Early versus delayed surgery in patients with left-sided infective endocarditis and stroke - Kremer, Jamila; Jahn, Joshua; Klein, Sabrina; Farag, Mina; Borst, Tobias; Karck, Matthias (Journal of cardiovascular development and disease, 2023)
Background: Timing of surgery remains controversial in patients with infective endocarditis and stroke. Guidelines on infective endocarditis suggest delaying surgery for up to 4 weeks. However, with early heart failure due to progression of the infection or recurrent septic embolism, urgent surgery becomes imperative. Methods: Out of 688 patients who were surgically treated for left-sided infective endocarditis, 187 presented with preoperative neurological events. The date of cerebral stroke onset was documented in 147 patients. The patients were stratified according to timing of surgery: 61 in the early group (0-7 days) vs. 86 in the delayed group (>7 days). Postoperative neurological outcome was assessed by the modified Rankin Scale. Results: Preoperative sepsis was more prevalent in patients with preoperative neurological complications (46.0% vs. 29.5%, p < 0.001). Patients with haemorrhagic stroke were operated on later (19.8% vs. 3.3%, p = 0.003). Postoperative cerebrovascular accidents were comparable between both groups (p = 0.13). Overall, we observed good neurological outcomes (p = 0.80) and a high recovery rate, with only 5% of cases showing neurological deterioration after surgery (p = 0.29). In-hospital mortality and long-term survival were not significantly different in the early and delayed surgery groups (log-rank, p = 0.22). Conclusions: Early valve surgery in high-risk patients with infective endocarditis and stroke can be performed safely and is not associated with worse outcomes.